Pengembangan Sistem Informasi Penerimaan Peserta Didik Baru Menggunakan Waterfall untuk Meningkatkan Efisiensi Pendaftaran - Faid, Mochammad; Setiawan, Novaldo Jaka; Alfiandri, Yanuar Ricky (Universitas Bumigora, 2024)
Background: Problems faced in the previous manual system include long queues, data inaccuracy, and slow administration, which hamper services to prospective students and parents. Objective: This study aims to improve the efficiency of the New Student Admissions (PPDB) process at Junior High School (SMP) Islam Abdul Wahid through the implementation of an online PPDB website. Method: The method used in this study is a software development approach with a waterfall model, which includes the stages of needs analysis, design, implementation, and system testing. Research data were obtained through interviews with administrative staff and questionnaires to prospective students and parents. This website is designed using web technologies to ensure reliability and ease of use. Result: The results of this study are that the online PPDB website is able to speed up the registration process, increase data accuracy, and significantly improve the service system. Conclusion: The conclusion of this study is that the implementation of the online PPDB website provides an effective solution in improving the efficiency of school administration and can be applied in other educational institutions as a form of digital innovation in the modern era.